Determinants of pulse wave velocity trajectories from youth to young adulthood: the Georgia Stress and Heart Study - Liang, Xiaohua (J Hypertens, 2019)
OBJECTIVE: Increased arterial stiffness measured by pulse wave velocity (PWV) has been shown to be an important parameter of cardiovascular risk. Longitudinal development of PWV from youth to early adulthood and its possible sociodemographic, anthropometric, hemodynamic and behavioral moderators will be illustrated. METHODS: Individual growth curves of carotid–distal PWV across age were created for 559 African American and European American men and women with a maximum of five assessments over an average of 7-year follow-up (mean age at participants’ first assessment, 22.3 ± 3.4). RESULTS: African Americans and men had significantly higher PWV than did European Americans and women (Ps < 0.01), respectively. A three-way interaction (P < 0.001) between age, sex and ethnicity was observed with African American men displaying a larger rate of increase in PWV with age than the other three ethnic and sex groups. The ethnicity and sex effects on PWV persisted when controlling for other moderators. Waist circumference was the strongest anthropometric predictor but its effect on PWV was only significant in women. Mean arterial pressure was the strongest hemodynamic predictor, marital status of parents was the strongest socioeconomic predictor and marijuana use was the strongest behavioral predictor of PWV. The best-fitting full model explained in total 59.4% of the between-subject variance in PWV with ethnicity, sex and age explaining 25.6%. CONCLUSION: We observed significant ethnic and sex differences in longitudinal trajectories of PWV in youth and young adults. In addition, individual differences in PWV growth can largely be explained by mean arterial pressure, waist, marital status of parents and marijuana use.